Isolation, abundance and phylogenetic affiliation of endophytic actinomycetes associated with medicinal plants and screening for their in vitro antimicrobial biosynthetic potential - Passari, Ajit K.; Mishra, Vineet K.; Saikia, Ratul; Gupta, Vijai K.; Singh, Bhim P. (Frontiers in Microbiology, 2015)
Microorganisms associated with medicinal plants are of interest as the producers of important bioactive compounds. To date, the diversity of culturable endophytic actinomycetes associated with medicinal plants is in its initial phase of exploration. In this study, 42 endophytic actinomycetes were isolated from different organs of seven selected medicinal plants. The highest number of isolates (n=22, 52.3%) of actinomycetes was isolated from roots, followed by stems (n=9, 21.4%), leaves (n=6, 14.2%), flowers (n=3, 7.1%) and petioles (n=2, 4.7%). The genus Streptomyces was the most dominant among the isolates (66.6%) in both the locations (Dampa TRF and Phawngpuii NP, Mizoram, India). From a total of 42 isolates, 22 isolates were selected for further studies based on their ability to inhibit one of the tested human bacterial or fungal pathogen. Selected isolates were identified based on 16S rRNA gene analysis and subsequently the isolates were grouped to four different genera; Streptomyces, Brevibacterium, Microbacterium and Leifsonia. Antibiotic sensitivity assay was performed to understand the responsible antimicrobials present in the isolates showing the antimicrobial activities and revealed that the isolates were mostly resistant to penicillin G and ampicillin. Further, antimicrobial properties and antibiotic sensitivity assay in combination with the results of amplification of biosynthetic genes polyketide synthase (PKS-I) and nonribosomal peptide synthetase (NRPS) showed that the endophytic actinomycetes associated with the selected medicinal plants have broad-spectrum antimicrobial activity. This is the first report of the isolation of Brevibacterium sp., Microbacterium sp. and Leifsonia xyli from endophytic environments of medicinal plants, Mirabilis jalapa and Clerodendrum colebrookianum. Our results emphasize that endophytic actinomycetes associated with medicinal plants are an unexplored resource for the discovery of biologically active compounds.